The function is continuous at 0 so the left hand limit is just the same as the right hand limit, and the limit exists at 0.

`lim_(x -> 0) (1+5/x)^x`

This is an indeterminate for of type `infty^0` . To resolve this, we perform the following transformation:

`lim_(x->0)(1+5/x)^x = e^(lim_(x->0)log(1+5/x)^x) = e^(lim_(x->0)xlog(1+5/x))` , using also the property of logarithms.

The resulting expression is still an indeterminate, this time, of type `0*infty` . We perform a substitution. Let `a = 1/x` . We now have:

`e^(lim_(x->0)xlog(1+5/x)) = e^(lim_(a -> +infty) (log(1+5a))/(a))`

This is still an indeterminate form, `infty/infty` but is easier to resolve. We simply have to use L'Hospital's Rule:

`lim_(a->+infty) (log(1+5a))/a = lim_(a->+infty) ((d(log(1+5a)))/(da))/((d(a))/(da))`

`lim_(a->+infty) (5/(1+5a))`

Note that the limit of a quotient is just the quotient of the limits, and the limit of the constant is same as the constant. Also, remember to bring back the whole expression (base e):

`e^(5/(lim_(a->+infty)(1+5a)))`

`lim_(a->+infty)(1+5a)` is infinity, so the entire exponent approaches 0. Therefore:

`lim_(x->0)(1+5/x)^x = e^0 = 1`

[Note that log here is the natural logarithm, ln]

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.